Hubungan Antara Malaria Klinis Dengan Anemia Pada Penderita Yang Berkunjung Di Puskesmas Wori Kabupaten Minahasa Utara - Mongi, Monica Michiko; Rombot, Dina V; Lampus, Benedictus S.; Umboh, Jootje M.L.; Kaunang, Wulan P.J.; Pandelaki, A.J. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2014)
Malaria remains a important public health problem in the world. Distribution of malaria depend on interaction betweenagent,host, and environment. Malaria is one of the indicators of the targeted Millennium Development Goals(MDGs) to stop the distribution of malaria. Assume of malaria case in Regency North Minahasa is 5.925 cases. Thepurpose of this study to analyze Relationship Between Clinical Malaria with Anemia in Patients Visiting Health CentersWori Regency North Minahasa. Design of this study using the cross sectional analytic study. Sample was determinedby purposive sampling. Total of sample is 50 respondent. Bivariate analysis using Chi Square, SPSS 20 version.The result showed that there is a Relationship Between Clinical Malaria with Anemia in Patients Visiting Health CentersWori Regency North Minahasa with a value of p=0.045(<0.05). Percentage of malaria with anemia 10% and percentageof malaria without anemia 0%. Percentage of negative malaria with anemia 48% and percentage of negativemalaria without anemia 42%. Conclusion : The result showed that there is a Relationship Between Clinical Malariawith Anemia in Patients Visiting Health Centers Wori Regency North Minahasa. Ha accepted and Ho rejected.Keywords: malaria, anemia